FOOD AND NUTRITION ACTIONS EDUCATION ACTIONS IN SCHOOLS ASSISTED BY THE SCHOOL HEALTH PROGRAM (PSE) IN THE MUNICIPALITY OF MACEIÓ (REMUNOM, 2025)
The Food and Nutrition Education (FNE) aims to promote the health and quality of life of students in the public education system by integrating actions from the health and education sectors. NFE is fundamental in this context, contributing to the development of healthy eating habits. Objectives: To identify the schools assisted by the PSE in the municipality of Maceió; To quantify the schools that carried out NFE actions in 2023; To evaluate the profile of these actions and the frequency of their implementation; and to verify the presence of a nutritionist in the planning and execution of the actions. Material and Methods: This is a descriptive ecological study using secondary data from the Primary Health Care Information System (SISAB). NFE actions carried out in 2023 in schools served by the PSE in Maceió were analyzed. Data collection also included technical visits to the Municipal Health Department to understand the planning and execution processes of the actions. Data analysis followed stages of tabulation, validation, and interpretation, according to established methodologies. Results and Discussion: Out of the 251 schools in the municipality of Maceió, 109 are assisted by the PSE. In 2023 30 schools carried out NFE actions, totaling 139 interventions that benefited 4,151 students. It was observed that only 30% of the schools with NFE activities have Primary Health Care (PHC) coverage, which may limit the integration between health and education. The presence of a nutritionist is designated for every 10 to 15 schools, acting as technical support. The NFE actions used playful materials and included training for the teaching staff, although there are challenges related to the feeding of SISAB by health teams. To strengthen NFE actions in the PSE in Maceió, it is essential to expand PHC coverage in schools, ensure the adequate presence of nutrition professionals, and improve the registration and monitoring processes of activities.